Development of SSR Marker Set to Identify Fourty Two Indonesian Soybean Varieties - Andari Risliawati; Eny I. Riyanti; Puji Lestari; Dwinita W. Utami; Tiur S. Silitonga (Jurnal AgroBiogen, 2015)
Profile of molecular marker can be used for variety identification, genetic purity monitoring of germplasm and additionalrequirement in proposing intellectual property protection. DNA fingerprinting of soybean had been applied at the ICABIOGRADIAARDsince 2004 using simple sequence repeat (SSR) markers which were run automatically by CEQ 8000 Genetic Analyzerplatform based on capillary electrophoresis system. This method had produced unique DNA fingerprints of the varieties tested,but the marker set to efficiently identify the varieties had not yet been developed. This study aimed to develop a set of SSRmarkers as a tool to identify the Indonesian soybean varieties. Fourty two soybean varieties were analyzed using 14 random SSRmarkersA total of 168 alleles that were obtained from the polymorphism analysis. The average of polymorphic informationcontent (PIC) value observed was 0.7337 per SSR locus. Based on marker reproducibility rate, PIC value, number of rare alleles,frequency of dominant alleles, and percentage of SSR fragment detected by genetic analyzer, we identified five SSR markers i.e.Satt414, Satt147, Satt308, Satt009, and Satt516 as a SSR marker set to be used for soybean variety identification purposes. Thismarker set was used to develop the identity (ID) of the 42 Indonesian soybean varieties.